Analysis of Lazismu's Performance in Alleviating Poverty in Makassar City - Arpa, Umu Aiman; Kasim, Muhammad Najib; Rahmah , Syahidah (Jurnal Economic Resource, 2025)
This study analyzes the performance of LAZISMU in alleviating poverty in Makassar City. With a quantitative approach and explanatory research type, this study aims to describe and analyze the relationship between LAZISMU performance (independent variable) and poverty alleviation (dependent variable). Secondary data were obtained from LAZISMU Makassar, supplemented by primary data through interviews. The location of the study was at the LAZISMU Makassar office, for 2 months. The population of mustahik was 1,875 people, with a sample of 95 respondents taken through purposive sampling and the Slovin formula. Data collection techniques used documentation and questionnaires (Likert scale). LAZISMU performance was measured by institutional trust, management quality, ZIS utilization, and donor services, while poverty alleviation was measured by housing conditions, access to education, health, and employment of beneficiaries. This study is expected to provide a comprehensive understanding of LAZISMU's contribution to poverty alleviation in Makassar.